Full‐length genomic sequence analysis of new subtype 3k hepatitis E virus isolates with 99.97% nucleotide identity obtained from two consecutive acute hepatitis patients in a city in northeast Japan. Issue 6 (26th December 2016) - Miura, Masahito; Inoue, Jun; Tsuruoka, Mio; Nishizawa, Tsutomu; Nagashima, Shigeo; Takahashi, Masaharu; Shimosegawa, Tooru; Okamoto, Hiroaki
Abstract : Full‐length genomic sequences of hepatitis E virus (HEV) obtained from two consecutive cases of acute self‐limiting hepatitis E in a city in northeast Japan were determined. Interestingly, two HEV isolates from each patient shared nucleotide identity of 99.97% in 7 225 nucleotides, and a phylogenetic analysis showed that they formed a cluster of Japanese isolates that is considered as a new HEV subtype 3k. The high similarity of HEV sequences of two isolates from these patients in this study suggested that a subtype 3k HEV strain had spread via a commonly distributed food in the city, possibly pig liver.